2022
DOI: 10.21203/rs.3.rs-1429599/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcranial electrical stimulation effects on neurovascular coupling

Abstract: Transcranial electrical stimulation (tES) can exert cerebrovascular effects, but the mechanisms are unclear. Long-term (≥3min) transcranial direct current stimulation (tDCS) can also change the extracellular ion concentrations that can modulate neuronal excitability. An increase in interstitial K+ can modulate the neurovascular system's sensitivity via Kir channels in the astrocytes and the mural cells.To gain a mechanistic understanding of the tES effects on neurovascular coupling (NVC), we used a physiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In addition, many studies run the models on the example head included with ROAST or an individual sample from the investigators. These work cover various clinical applications including: attention-deficit hyperactivity disorder [ 61 , 62 ], aging [ 63 ], associative memory [ 64 , 65 ], attention [ 66 – 68 ], body awareness [ 69 ], cognitive control and function [ 70 ]; Fusco et al [ 125 ]; [ 71 , 72 ], connectivity [ 73 ], decision making [ 74 77 ]; Schulreich and Schwabe [ 126 ], declarative learning [ 78 ], depressive disorder [ 79 ], electroencephalography (EEG) research [ 80 83 ], imitation [ 84 ], memory retrieval [ 85 87 ], mind wandering [ 88 , 89 ], motor learning [ 90 95 ], motor skills [ 96 98 ], neurorehabilitation [ 60 ], neurovascular coupling [ 99 ], obsessive-compulsive disorder [ 100 ], phantom limb pain [ 101 ], post-anoxic leukoencephalopathy [ 102 ], reading speed [ 103 ], schizophrenia [ 104 ], social anxiety disorder [ 105 ], stroke [ 106 ], visual perception [ 107 , 108 ], and working memory [ 109 115 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, many studies run the models on the example head included with ROAST or an individual sample from the investigators. These work cover various clinical applications including: attention-deficit hyperactivity disorder [ 61 , 62 ], aging [ 63 ], associative memory [ 64 , 65 ], attention [ 66 – 68 ], body awareness [ 69 ], cognitive control and function [ 70 ]; Fusco et al [ 125 ]; [ 71 , 72 ], connectivity [ 73 ], decision making [ 74 77 ]; Schulreich and Schwabe [ 126 ], declarative learning [ 78 ], depressive disorder [ 79 ], electroencephalography (EEG) research [ 80 83 ], imitation [ 84 ], memory retrieval [ 85 87 ], mind wandering [ 88 , 89 ], motor learning [ 90 95 ], motor skills [ 96 98 ], neurorehabilitation [ 60 ], neurovascular coupling [ 99 ], obsessive-compulsive disorder [ 100 ], phantom limb pain [ 101 ], post-anoxic leukoencephalopathy [ 102 ], reading speed [ 103 ], schizophrenia [ 104 ], social anxiety disorder [ 105 ], stroke [ 106 ], visual perception [ 107 , 108 ], and working memory [ 109 115 ].…”
Section: Resultsmentioning
confidence: 99%
“…of the cerebral surface area and the cerebellar gray matter volume (Buckner et al, 2011), which needs future investigation based on fNIRS directed functional connectivity (specifically, subserved by the ventral superior longitudinal fascicle SLF III (Kamat et al, 2022b)) vis-à-vis error-related perception action coupling. Also, tDCS effects on the extraneuronal milieu in neurovascular unit (Arora and Dutta, 2022) needs investigation where a POS-PRE decrease in the left prefrontal scalp EEG activity (within 1-40Hz and 1-5sec at the start of the FLS task) was found to be related to an increase in the left prefrontal HbO cortical activation (from 5-15sec) see Figures 5f and 6a. Notably, the left prefrontal scalp ERSP changes were partly driven by the EEG frequencies below 8Hz (e.g., theta activity) as seen in the Figures 5e and 5g.…”
Section: Table 2 Here Figure 5 Here Figure 6 Here 4 Discussionmentioning
confidence: 99%
“…It may also be possible that the intra-subject variability in the current distribution maps is in part due to the current-induced hemodynamic effects in the brain. Previous studies have shown that transcranial electrical simulation can evoke transient changes in the cerebral blood flow and blood volume (Zheng et al, 2011 ; Arora et al, 2021 ; Arora and Dutta, 2022b ), which could in turn affect the current path by altering the overall conductivity of the neurovascular tissue.…”
Section: Discussionmentioning
confidence: 99%